2018
DOI: 10.1016/j.amsu.2018.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance patterns, challenges, and outcomes of fracture management in osteopetrosis patients. CASE series and review of pertinent literature

Abstract: BackgroundOsteopetrosis (OP) is a group of rare inheritable genetic disorders which show increased bone radiodensity on radiography. As no cure exists, careful symptomatic treatment is the mainstay in management due to brittle bone and frequent complications. We would like to present a case series of OP patients, their management, a review of literature about this rare disease and its genetic and inheritance patterns.Materials and methodsRetrospective case series of 6 patients with OP seen at our institution f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
9
0
2
Order By: Relevance
“…Further adding to the plight, the standards and principles for the treatment of fractures in patients with osteopetrosis are not yet clearly formulated[ 7 ]. Armstrong et al [ 8 ] conducted a survey of the membership of the Pediatric Orthopedic Society of North America, which incorporated the experience of 57 surgeons who treated 79 fractures in patients with osteopetrosis, with their findings illustrating that the majority of patients with osteopetrosis were successfully treated using the conservative approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further adding to the plight, the standards and principles for the treatment of fractures in patients with osteopetrosis are not yet clearly formulated[ 7 ]. Armstrong et al [ 8 ] conducted a survey of the membership of the Pediatric Orthopedic Society of North America, which incorporated the experience of 57 surgeons who treated 79 fractures in patients with osteopetrosis, with their findings illustrating that the majority of patients with osteopetrosis were successfully treated using the conservative approach.…”
Section: Discussionmentioning
confidence: 99%
“…There is a certain risk of drill bit breakage and iatrogenic fracture during the operation, which can lead to failure of treatment[ 9 - 12 ]. However, as long as preoperative preparations and corresponding surgical strategies are well formulated in a timely manner, surgical treatment is still heralded as the first-choice treatment for fractures in patients with osteopetrosis[ 7 , 18 , 19 ]. Unfortunately, regardless of whether the operation is successful or not, the risk of delayed union or even nonunion still persists[ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plate osteosynthesis, intramedullary nailing and total joint arthroplasty are all suitable options. Hasan et al (24) provided a summary of the difficulties in treating OP fractures, including broken/bent drill bits, infection, hard bone, bone overheating, periprosthetic fracture, slow healing of fracture and narrow medullary canal, and concluded that plate osteosynthesis may be preferred.…”
Section: Discussionmentioning
confidence: 99%
“…A sequence of treatments, progressing from drainage, antibiotic therapy, sequestrectomy, tooth extraction, saucerization, decortication, to bone resection and oxygen therapy, has been proven to be valuable in the management of osteomyelitis (26). For patients with benign OP, non-operative treatment options include hip spica plaster cast, traction, splint and avoidance of weight bearing (24). A low-calcium diet can create a calcium-absorptive state and calcitriol can stimulate bone resorption, which may delay the process of bone sclerosis (27).…”
Section: Discussionmentioning
confidence: 99%